Zinc finger protein 32 promotes breast cancer stem cell-like properties through directly promoting GPER transcription. Issue 12 (December 2018) - Li, Yanyan; Gong, Di; Zhang, Le; Li, Hongjiang; Zhang, Shu; Zhang, Jie; Li, Kai; Zheng, QianWen; Zhao, Gang; Zhang, Yue; Chen, Yue; Guo, Yafei; et al.
Abstract Breast cancer is one of the leading causes of death in women. Due to the existence of a small fraction of stem cell-like subpopulations, some breast cancer subtypes exhibit very high malignancy and resistance to multiple therapies. The underlying mechanisms of how these subtypes acquire stem cell-like properties and progress more aggressively remain largely unknown. Zinc finger protein 32 (ZNF32), a newly discovered transcription factor, has been reported to be associated with breast cancer progression. However, many questions remain about its target genes and its exact mechanisms in regulating stem cell-like properties and drug resistance. In the present study, we examined the relationship between ZNF32 and GPER, a membrane-associated estrogen receptor, and we addressed their roles in stemness regulation in human breast cancer cell lines. Our results showed that ZNF32 could induce expansion of stem cell-like subpopulations and increase drug resistance by upregulating GPER expression, in which ERK activation was also implicated. We also illustrated that ZNF32 induced GPER expression via a ZNF32 binding sequence located within the GPER promoter region. A correlation between ZNF32/GPER expression and increased tumor incidence and burden was observed in xenograft mouse models. We conclude that ZNF32 can engage GPER/ERK signalling and confer breast cancer stem cell-like properties, which may indicate poor prognosis of breast cancer patients. ZNF32 and GPER targeted therapies might provide new solutions for breast cancer treatment.